Design and characterization study of LaFeO3 and CaTiO3 composites at microwave frequencies and their applications as dielectric resonator antennas. Issue 23 (1st December 2021) - Azevedo, L.O.; Vasconcelos, S.J.T.; Andrade, H.D.; Júnior, I.S. Queiroz; Silva, R.S.; Sombra, A.S.B.
Abstract: Technological development leads to the demand for innovation and the discovery of new materials properties. In telecommunications, DRAs (antennas with a dielectric block as radiant element) are a viable option for high frequency applications, where low profile and low losses are desirable, and essential requirements in several cases. A study of the properties of composites of lanthanum ortoferrite LFO (LaFeO3 ) and calcium titanate CTO (CaTiO3 ) as cylindrical dielectric resonator antennas is presented for the first time. In order to carry out the analysis, the material was produced through the solid state route, and resonators of LFO-CTO solid solutions were manufactured for seven different values of CTO weight fraction (0; 0.15; 0.20; 0.36; 0, 56, 0, 60 and 1). X-ray diffractometry, dielectric characterization, measurement of antenna parameters and subsequent comparison of measured values with theoretical and simulated values were performed. The antennas in this work showed good gain, good impedance matching, consistent values of return loss, high temperature stability and resonance frequency; all operating at the S band and beginning of the C band of the microwave spectrum.